New Ijtihad of Islamic Education: Analysis of Rabbaniy Curriculum Concepts and Tazkiyah An-Nafs Learning Model - Arif, Khairan Muhammad (Ikatan Dai Indonesia, 2025)
This study aims to find and introduce new concepts and thoughts about the Rabbani curriculum and the Tazkiyah An-Nafs learning model in Islamic education sourced from the Qur'an and As-Sunnah, this research also aims to present solutions to the problem of the vacuum of Islamic education concepts, especially in the curriculum and learning models faced by the Islamic world due to the monoconcepts that apply in education today. This research method uses a type of qualitative research method , with a descriptive analysis approach which aims to analyze and test then explain the theory or concept offered as a solution, namely the Islamic education curriculum sourced from Allah swt called the rabbaniy curriculum based on the Qur'an and Hadith. The Tazkiyah An-Nafs learning model is a learning model based on one of the teachings of the Qur'an which emphasizes cleansing the soul. This research is carried out critically, authentically, literatively and thematically, as well as analyzing and explaining scientifically and objectively all data sources, so as to produce synthesis and tested scientific conclusions. The source of this research is the library by tracking and studying the Qur'an and Hadith along with their tafsir and other references related to the theory and concept of curriculum and learning models of Islamic education in addition to conventional education. The result of this study is that the rabbaniy curriculum based on the Qur'an and Hadith turns out to be more inregral and holistic in developing student personality, because the rabbaniy curriculum is more humanistic and in accordance with student development psychology. Tazkiyah An-Nafs' wahyu based learning model turns out to better answer the challenges of students' psychological, faith and moral problems in global era that is experiencing moral and cultural degradation.